A teacher in the mirror of a psychologist - Stanković Đorđević, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Snežana Stojiljković, Psychological characteristics of a teacher, Faculty of Philosophy of Niš, Niš, 2014, 340 pp.This article presents the monograph of prof. Dr. Snežana Stojiljković Psychological characteristics of teachers, in which the author, following the thread of her scientific interests provides a comprehensive picture of characteristics and competencies of educators. Beginning with teacher's role as the carrier of educational activities and psycho-social portrait of future teachers, and through analysis of the educational role of a teacher, to the psychological characteristics and considerations of professional stress of teachers. The special value of this part make presentations of research, most of which are carried out by the author herself and her associates. Stojiljkovic argues that teachers are fairly homogeneous population, which have the characteristics of members of the helping professions and she highlights the importance of examining the personality dimensions relevant to the teaching profession, both for professional orientation, as well as for achievement of development potential of teachers. The author of this monograph concludes with the topic related to the readiness of teachers for professional development. The significance of the monograph can be seen in actuality of the topic she is dealing with. It represents both a polemic and an invitation to reconsider the usual stereotypes about the role and place of teachers, by which the author enters into a dialogue with potential readers and encourages personal review and reflection on their own educational practice and place in society.